Analysis of factors affecting the success rate of open defecation free (ODF) and ODF target achievement in Binangun, Blitar Regency - Rahma, Ita Nur; Fasya, Abdul Hakim Zakkiy (Universitas Nahdlatul Ulama Surabaya, 2023)
Health development, especially in the field of hygiene and sanitation, is a major challenge faced by Indonesia. By 2030, Indonesia has a target to end open defecation free (ODF). ODF achievements in Indonesia have decreased over the past 10 years The purpose of this study is to analyze the factors that influence the success rate of ODF in Binangun Subdistrict, Blitar District. This study used descriptive quantitative research with a Cross Sectional approach. The data used were primary data obtained by conducting direct observations and interviews. Data analysis used univariate and multivariate analysis using Partial Last square (PLS). However, there is an influence between external variables on behavioral beliefs, external variables on normative beliefs (f-square 0.090). Demographic variables on behavioral beliefs (f-square 0.010). Demographic variables on normative beliefs (f-square 0.033). Behavioral beliefs on attitude (f-square 0.004). Normative beliefs to subjective norms (f-square 0.033). Attitude to behavior (f-square 0.335). Subjective norm to behavior (f-square 0.022). Behavior to ODF success (f-square 0.171). Based on the results of this study, it can be concluded that there is a large influence between external variables on behavioral beliefs and normative beliefs, attitudes towards behavior, behavior towards ODF success. There is a moderate influence between demographic variables on normative beliefs, normative beliefs on subjective norms, subjective norms on behavior. There is a small influence between demographic variables on normative beliefs, behavioral beliefs on attitudes. It is suggested that further researchers conduct coaching and visits to the community to increase the awareness of environmental health.